Motor Noise and Vibration Test Research - Zhongjie Wang; Jingnan Zhang; Yongchun Liang (Universitas Ahmad Dahlan, 2013)
Some factors, such as friction, vibration, and so on, can result in the fault and abnormal noise in the motor. Based on the detection and analysis of noise and vibration, we can identify and eliminate the faults of the motor. This is helpful not only to ensure the completion of production tasks, but also to prevent accidents. In this paper, we briefly introduce the motor noise generation principle. A laptop computer and LabVIEW software are used to design the experiment system to detect and analysis the noise and vibration of motor. External microphone and computer with sound card constitute noise detection system hardware. Vibration sensor and the data acquisition card constitute vibration detection system hardware. LabVIEW software combined with FFT analysis is used to realize the noise signal acquisition, recording and spectral analysis. Detecting and analyzing the noise of the permanent magnet DC motor and three-phase asynchronous motor proves that the motor noise and vibration detecting experimental platform is fully meet the requirements of motor test and research. This detection and analysis system has a good man-machine interface and strong operability.